The impact of demand deposit and time deposit on the statutory reserve requirement / Hasri Mustafa @ Abdul Razak - Mustafa @ Abdul Razak, Hasri (1994)
This is an analytical study done to identify the factors determining the movement of Statutory Reserve Requirement.Demand deposit and time deposit are selected as independent variables using Multiple Regression in order to see their relationship with Statutory Reserve Requirement for the year of 1981 - 1994.Prior to that, Karl Brunner and Allan Meltzer Prototype is applied to indicate the nature of the variables of demand deposit and time deposit in related with Statutory Reserve Requirement. This study also includes calculations to measure the probable effect given in the percentage in demand deposit and time deposit to Statutory Reserve > Requirement by using Elasticity method. This project paper then will be closed with some conclusions and recommendations in related with the finding obtained through those above method analysis.